Ways of living religion philosophical investigations into religious experience - Gschwandtner, Christina M. 1974- (Cambridge University Press, 2024)
"Ways of Living Religion provides a philosophical analysis of different types of religious experience, focusing on the lived experience of religion rather than mere statements of belief or doctrine. Christina M. Gschwandtner distinguishes between experiences by examining their defining features, showing their continuity with human experience"